Development of a novel system for linear displacement sensor calibration. (February 2019) - Lagozzino, Samsone; Simic, Milan; Dudkiewicz, Dominik
Abstract: This paper presents the development of semi-autonomous metrological devices, capable of calibrating variety of linear displacement sensors, like Linear Variable Differential Transformers (LVDT), string potentiometers, laser displacement sensors and other. Data acquisition equipment that could be used for measuring objects of various shapes and sizes are already available; however, devices specifically tailored for the calibration of displacement sensors are not currently offered. Advantages of this new technology, that we are investigating and developing, include reduction of time, costs and human resources required to perform calibration. In addition to that, the advantages of an affordable calibration device will allow calibrations to be carried out internally, as opposed to outsourcing to dedicated facilities. The scope of the project encompasses research into the device's compliance with ISO/IEC 17025 to obtain NATA accreditation, research into design, and selection of material and manufacturing processes to ensure an acceptable measurement of uncertainty is achievable across all varieties of linear displacement sensors. The sensors are used to measure suspension displacement, steered angle and various other geometries on vehicles and test equipment. Outcomes of this research project offer experimental evidence that proves the feasibility of developing and manufacturing devices that produce an acceptable uncertainty that meets testing standards requirements at a fraction of the cost of comparable measuring devices.